Strategi Adaptasi Berkelanjutan terhadap Perubahan Iklim di Sektor Pertanian Indonesia - Nirwana Langi; Sri Ayu Lestari; Islamul Hadi; Evy Aryanti (Jurnal Pendidikan, Sains, Geologi, dan Geofisika (GeoScienceEd Journal), 2026)
Climate change has become one of the major challenges in the development of the agricultural sector in Indonesia, as it directly affects productivity, production stability, and farmers’ welfare. The increasing frequency of extreme events such as droughts, floods, and shifting rainfall patterns has led to higher risks of crop failure and ecosystem degradation. Therefore, sustainable adaptation strategies are required to enhance the resilience of the agricultural sector while supporting long-term development. This article aims to analyze various sustainable adaptation strategies in Indonesia’s agricultural sector, including community-based approaches, the application of climate-smart agriculture technologies, income diversification, as well as financial and policy support. Furthermore, this study links these strategies to the achievement of the 17 Sustainable Development Goals (SDGs), particularly in areas such as food security, poverty alleviation, climate action, ecosystem protection, and global partnerships. The findings indicate that the integration of comprehensive and collaborative adaptation strategies can improve farmers’ resilience to climate change, strengthen national food security, and significantly contribute to the overall achievement of the SDGs. Therefore, synergy among the government, private sector, and communities is essential to establish a resilient and sustainable agricultural system in Indonesia.